Improving Students' Numeracy Literacy Ability in Physics Subjects - Sopacua, Venty; Sapulete, Heppy (Pascasarjana, Mataram University, 2025)
Numeracy literacy is one of the six basic skills that are prerequisites and life skills in the 21st century, for numeracy literacy in Indonesia is still relatively low and far behind other countries for that, numeracy literacy skills are important in physics subjects because physics is inseparable from mathematics. The purpose of this study was to determine the increase in numeracy literacy of SMA A Class XI IPA students in Physics. The approach in this study used a qualitative and quantitative approach with a descriptive analysis method. The sample in this study amounted to 26 students in class XI IPA-2 at SMA A, West Seram Regency. The instrument used was a test instrument consisting of 15 test questions that included numeracy literacy indicators on the material of material elasticity. The data analysis technique in this study was quantitative and qualitative data which were the main data of the study in the form of numeracy literacy skills before (pretest) and after (posttest). The results of the study showed that the average N-gain value was 0.45 and it was found that 2 students (8%) had numeracy literacy skills at the Skillful level, at the Provicient competency level there were 8 students (31%), at the basic competency level there were 13 students (50%), and at the competency level requiring special intervention there were 3 students (11%), so it can be concluded that there was an increase in the numeracy literacy skills of SMA A Class XI IPA-2 students in Physics with a low category and classified as a basic level.